"Guadua angustifolia Kunth: opción de diversificación productiva para productores en la Península de Osa, Costa Rica." - Arguedas-Chaverri, Andrés (Instituto Tecnológico de Costa Rica, 2015)
This study aims to promote technical and sustainable use of Guadua angustifolia stands in the Osa Peninsula, Costa Rica. An initial diagnosis of guadua plantations was performed. The potential for commercial use was assessed through a forest inventory and market analysis of bamboo culms within the Peninsula was performed. The effective area under study comprised7.45 Guadua ha from a total of 35.88 been analyzed, which means 79.2% mortality. Only 1.2 ha are suitable for commercial use with a total production supply of 1534 culms. The remaining 6.25 ha be exploited in the future, after a technical and appropriate management. The demand for 2015 is 1280 to 1 550 culmst by resorts and construction industry in the area. Finally, a list of recommendations for silvicultural management stands studied is presented, which was exposed on a silvicultural management workshop aimed at organized producers. However, an attendance of 17.9% of the target group was obtained, making the which remains the responsibility of the cooperative to bring this information to other producers.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2015.
Keywords: Manejo de plantaciones forestales; Manejo sostenible; Bambú; Extensión forestal; Rodales